JUSTIFICATION OF THE WORK OF A MOBILE APPLICATION FOR THE IMPLEMENTATION OF PRIMARY SELECTION FOR ENGAGEMENT IN VARIOUS SPORTS (Physical Culture and Sport: Scientific Perspective, 2025)
The article considers the problem of implementing primary selection for classes in sports sections. Analysis of special literature has shown that for primary selection the most important are simple, accessible tests (norms) that determine the morphological and motor capabilities of children. The preference is given to those indicators that indicate hereditarily determined signs of physical development.Among the effective steps aimed at improving primary selection, we consider the use of a mobile application to determine the feasibility of engaging in selected sports. The article describes in detail the work of such an application. Five main elements have been identified that ensure its operation: configuring the mobile application; downloading the application to mobile phones; measuring physical development indicators; processing the measurement results by the mobile application administrator; sending the processed information to students' mobile phones. Using this application provides information to the student regarding the appropriateness of engaging in sports that are cultivated in the local community. Determining the appropriateness of practicing the chosen sport is carried out using a standard scale and weighting factors.The application identifies three levels of appropriateness of engaging in sports: high, medium, and low. In addition to recommendations on the appropriateness of sports activities, the mobile application provides information on the addresses of sports facilities, class schedules, information about the school's sports achievements, information about the coaching staff, etc. The scope of application of the mobile application can be expanded by informing children about the launch of new sports in the city, holding sports competitions, demonstration performances, mass sports events, etc.
Keywords: primary selection in sports; mobile application; physical development; morphological indicators